唐代女穿男装现象研究 = The study of Tang Dynasty women wearing men's clothes - 郑蓓思 Tee, Bei Si (2009)
唐代女性的服饰主要是袒胸襦裙装、胡服以及男装。这三种服装都显示出唐代女性不同的审美心态和对传统思想的反叛。本文的重心是探讨唐代女性着男装的现象，这种现象的产生与唐代国力强盛、社会对外开放的态度、经济物质优越的条件有直接的关系。三教并举的思想文化政策更使唐代女性勇于冲破儒家思想对于女性的束缚，长期的多元文化的渗透使唐代出现了第一位女性的皇帝。武则天以女皇的权力使唐代女性在社会的地位上升,使女性在社会的自主权和女性意识的兴起。不同阶级的唐代女性着男装的原因也不同，而本文将依照她们的社会阶级而分类为三种类型来看出男装对于不同类型的女性的不同意义。第一类型的女性是握有政治权力及在社会享有高地位的，如武则天和太平公主，她们视男装为一种性别转换的武器来消除社会对于性别角色的认定。第二类型的女性便是有钱有势的贵族妇女，她们着男装的目的是为了跟上时尚，领导唐代女性服饰的潮流，纯粹是为了得到异性和同性的目光。第三类型的女性是社会地位较底的宫女民女，她们是被动地穿男装因为这是她们的制服之一和方便劳动。因此，唐代女穿男装反映的课题是关于妇女如何以男装来建构自己的身份，以及反映出男权语境中的女权意识。The main costumes for women in Tang Dynasty are wide-sleeve bosom exposed long dress, Hu’s style clothes and men’s clothing. These three different types of costumes represent the different aesthetic tastes and it is a sign of rebellion towards the Confucian culture. The main focus of this thesis is to analyze in-depth regarding the presence of men’s clothing being one of the main costumes of women in Tang Dynasty. Women donning in men’s clothes is consider in fashion for a time as a result of the great influence of the prosperous Tang Dynasty due to its rapid developing economy and frequent cultural exchange with other countries. Tang’s women are more liberated in their thinking due to the exposure of the different religions being introduced in Tang Dynasty, mainly Confucian, Taoism and Buddhism that brought a variety of different religious views. Due to Tang Dynasty’s long term multicultural exchange, Tang’s women became more conscious of women’s rights and feminism, thus it is reflected in their actions such as becoming more involved in the country’s political issues; holding important positions in the society; making daring changes in their clothing designs to express their freedom. As we know that costumes is a significant symbol of gender especially in ancient china where clothing regarding male and female is considered to be an important concept in Confucian culture.